Mekanisme Pertahanan Diri Tokoh Syekh Ali dalam Cerpen Thabliyyah min as-Sama’: Kajian Psikoanalisis Sigmund Freud: The Self-Defense Mechanism of Sheikh Ali in the Short Story Thabliyyah min as-Sama’: A Psychoanalytic Study by Sigmund Freud - Jasmiko, Jasmiko; Abshar, Ulil; Nurfariha, Firyal Nafisa; Fajrina, Amelia; Alawiyah, Alawiyah (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2025)
This study aims to analyse the forms of self-defence mechanisms used by the character of Sheikh Ali in the short story Thabliyyah min as-Sama' by Yusuf Idris using Sigmund Freud's Psychoanalytic approach. The main problem in this study lies in how psychological pressures in the form of poverty, failure, and social rejection shape Sheikh Ali's psychological response, and what types of self-defense mechanisms emerge as a result of the conflict. This study uses a qualitative descriptive method with content analysis techniques, where data in the form of narrative excerpts and character dialogues are analyzed to identify and classify the forms of self-defense mechanisms. The results show that Sheikh Ali uses ten self-defense mechanisms as proposed by Freud, namely repression, projection, rationalization, displacement, sublimation, denial, regression, reaction formation, identification, and compensation. This finding confirms that Sheikh Ali's inner conflict is the result of a dynamic interaction between the id, ego, and superego when faced with the stressful realities of life. This study offers a new perspective to investigate the short story Thabliyyah min as-Sama'. This study enhances our understanding of the representation of characters' psyches in Yusuf Idris's works and demonstrates that literature can be a valuable tool for studying human adaptive strategies for overcoming conflict and adversity. Therefore, this study expands the scope of research on Sigmund Freud's Psychoanalysis in contemporary Arabic literature, particularly in reading works related to socio-psychological topics.